Ukrainian health care system and its chances for successful transition from Soviet legacies - Piotr Romaniuk; Tetyana Semigina (BMC, 2018)
Abstract Background Ukraine, one of the largest states formed on the rubble of the Soviet Union, is widely perceived as a country that has lost its opportunities. Being devastated by corruption, it shows incapable to modernize and enter the economic path of sustainable growth. Similarly in the health care system no deeper reform efforts have been taken in the entire post-soviet period, leaving the system in bonds of ineffective solutions taken out of the Soviet era. Main body The recent geopolitical and economic crisis seem to favor the introduction of radical solutions that might lead to a rapid change in the organizational paradigm of the economic system, as well as in health care in Ukraine. In this paper we aim to highlight the key features of the ongoing health reform in Ukraine, identify basic challenges for it, and assess rationality and feasibility of the reform. We found that the projected scope and schedule of changes in the Ukrainian health system give promising prognosis regarding its final effect. Conclusions The final success of health reform in Ukraine is dependent on a number of factors, including the financial foundation arising of economic stability of the country, balance assurance between public and private spending for health and ability to eliminate the long-lasting practices, particularly when they are connected with activities of lobbying groups occupying particular positions in the health system. A consequence of actions taken by the political decision-makers in the longer perspective are also to highly determine the reform's chances for success.